Reconstruction of the Social Security System Policy in National Development of Indonesia - Hadiyat, Yayan; Herman (Journal of Social Transformation and Regional Development, 2024)
The implementation of social security and a decent living for the people of Indonesia, as mandated by the 1945 CONSTITUTION, Article 27, paragraph (2), has a long history with various policies and changes over time. It began with the issuance of Law No. 14/1969 concerning Basic Provisions Regarding Manpower, followed by Law No. 3/1992 concerning Social Security for Workers in Indonesia, and up to Law No. 13/2003 concerning Manpower. The social security system still includes social security protection for workers, while national social security for non-worker citizens is implemented sporadically in the form of assistance and social safety net programs with various forms of direct and indirect assistance activities. After the issuance of Law no. 40 of 2004 concerning the National Social Security System, Law No. 36/2009 concerning Health, and Law No. 24/2011 concerning the Social Security Administering Body, as well as their implementing regulations through Government Regulations, Ministerial Regulations, or Decrees, the national social security system policy has been reconstructed in an integrated manner to realize a national social security system for all Indonesian citizens. The role of the government in handling the Covid-19 pandemic from late 2019 to early 2021, with its various policies, has proven that there is a relationship between the existence of a national social security system and economic growth. Socio-economic impacts during the Covid-19 pandemic can be suppressed, and the economy can still grow with various social security policies and health care insurance. However, in the absence of a more comprehensive government policy to create a national social security system, the negative impact on the people’s economy continues to occur, driving up the poverty rate. Therefore, the implementation of the national social security system needs to be carried out in a more comprehensive manner, namely by adding the provision of life insurance, accident insurance, and old age insurance for citizens who are not wage earners. This way, they can continue to carry out productive activities with guarantees for themselves and their families. This policy will guarantee the social life of all citizens and will directly or indirectly guarantee the activity and growth of the national economy.